Exacerbation of murine ileitis by Toll-like receptor 4 mediated sensing of lipopolysaccharide from commensal Escherichia coli. Issue 7 (25th January 2007) - Heimesaat, M M; Fischer, A; Jahn, H-K; Niebergall, J; Freudenberg, M; Blaut, M; Liesenfeld, O; Schumann, R R; Göbel, U B; Bereswill, S
Abstract : Background: In the course of inflammatory bowel diseases (IBD) and acute murine ileitis following peroral Toxoplasma gondii infection, commensal Escherichia coli accumulate at inflamed mucosal sites and aggravate small intestinal immunopathology. Aim: To unravel the molecular mechanisms by which commensal E coli exacerbate ileitis. Methods: Ileitis was investigated in mice that lack Toll-like receptors (TLR) 2 or 4, specific for bacterial lipoproteins (LP) or lipopolysaccharide (LPS), respectively. Gnotobiotic mice, in which any cultivable gut bacteria were eradicated by antibiotic treatment, were used to study the role of LPS in ileitis. Results: Microbiological analyses revealed that E coli increase in the inflamed ileum. TLR4 −/−, but not TLR2 −/−, mice displayed reduced mortality and small intestinal immunopathology. Decreased interferon (IFN)-γ and nitric oxide (NO) levels in the inflamed terminal ileum of TLR4 −/− mice indicated that TLR4 signalling aggravates ileitis via local mediator release from immune cells. E coli strains isolated from the inflamed ileum activated cultured mouse macrophages and induced TLR4-dependent nuclear factor κB activation and NO production in human embryonic kidney 293 cells and in peritoneal macrophages, respectively. Most strikingly, in contrast with wild-type mice, gnotobiotic TLR4 −/− mice were protected from induction of ileitis by treatment with purified E coli lipid A or colonisation with live E coli . Finally, prophylactic treatment with the LPS scavenger polymyxin B ameliorated T gondii -induced ileitis. Conclusion: These findings highlight the innate immune system as a key player in T gondii -induced ileal immunopathology. Treatment with LPS or TLR4 antagonists may represent a novel strategy for prophylaxis and/or therapy of small intestinal inflammation in IBD.